Métodos de propagação, espaçamento e densidade de plantio de jambu - Sampaio, Italo Marlone Gomes (2017)
In the current context of vegetables production in Brazil, it may be seen a wide variety of crops; some of them have great acceptance (traditional crops), whereas others have minor importance (nontraditional crops), the production and commercialization of this last group is limited to small markets, which occurs, usually, in villages located at the countryside of Brazil. Jambu (Acmella oleracea (L.) R. K. Jansen) is a good example of nontraditional crops. It is mostly produced in the states of the Amazon. Its productive impact is remarkable in the North Region of Brazil, especially in the state of Pará, where it plays an important role in gastronomy. Nevertheless, the species still lacks in-depth information about its proper production. Thus, this work aims to assess the development of seedlings of jambu in different plant growing trays and sowing densities, as well as the effect of plant density and number of plants per planting hole on yield. Three essays were carried out in the vegetable garden of the Federal University of Ceará, campus of Pici, Fortaleza, state of Ceará, Brazil. In the first essay, the production and quality of jambu seedlings produced in different plant growing trays was studied. In the second one, we analyzed the influence of sowing density on production and quality of jambu seedlings. In the third experiment, we studied the influence of plant density and the number of plants per planting hole on the production of jambu. The tray with 162 cells provided the best quality seedlings. The best quality of seedlings was observed starting with the production density of two plants per cell. The spacing between plants of 0.2 × 0.2 m with the highest number of plants per planting hole, 12 plants, lead to the highest production.